Low-intensity with Practical Blood Flow Restriction Strength Protocols Successfully Increases Maximal Isometric Strength in Both Upper and Lower Muscles : A Pilot Study - Longrak, Ratanyoo; Sonchan, Wirat; Jaidee, Watanya (Interprofessional Journal of Health Sciences, 2024)
This pilot study investigated the efficacy of a short-course minimal strength-protocol utilizing practical blood flow restriction, aiming to optimize muscle strength gains within a limited timeframe. The participants included 8 healthy undergraduate individuals undergoing the training intervention, and whose baseline strength levels were evaluated before the study. The intervention spanned three weeks, with a single session per week, and comprised a combination of high-intensity and low-intensity exercises with practical blood flow restriction. The results revealed significant improvements in both elbow flexor and knee extensor muscle strength postintervention (p < 0.05), with notable percentage increases recorded. Specifically, participants demonstrated enhancements of approximately 24.94% in elbow flexor strength and 23.08% in knee extensor strength in the limited timeframe. These findings demonstrated the practical applicability of the protocol in diverse settings, emphasizing its potential as a time-efficient strategy for maximizing muscle strength gains within a limited training period.